Impact of Economic Factors and Policy Interventions on the COVID-19 Pandemic - Yupeng Li (MDPI AG, 2021)
This paper studies how policy interventions and economic factors affect COVID-19 infections and deaths, using generalized linear regression (GLM) models. We seek to explain the containment differences by countries’ inherent economic factors, especially the labor market structure, utilizing data from multiple sources. The results show that countries heavily relying on the service sector and international trade suffer more from the spreading, possibly due to the fact that COVID-19 is a communicable disease and spreads quickly through physical contact. Further, we find that these countries could benefit more from stringent policies compared to others.